Failure analysis of electric motor due to excessive shaft load using the FMEA method in rice milling units - Sunaryo Sunaryo; Wisnu Yogi Pangestu; Abrar Ridwan (Jurnal Polimesin, 2026)
While Failure Mode and Effect Analysis (FMEA) has been widely applied in heavy industries, its application in the mid-scale agro-industrial sector remains highly limited. This study addresses this critical gap by analyzing the mechanical failure of electric motors in Rice Milling Units (RMUs) within the Lappariaja District, focusing specifically on the synergistic impact of excessive shaft loading and high-particulate environments on motor longevity. Adopting a descriptive quantitative approach, this research integrates multi-modal data collection, including field observations, technical measurements using digital multimeters, and operator interviews. The FMEA framework was applied to calculate the Risk Priority Number (RPN) for each prominent failure mode. The empirical findings reveal that the Stator Winding is the most critical vulnerability, with the highest RPN of 252, due to a severe "thermal trap" phenomenon in which rice husk dust acts as an unwanted thermal insulator. This is closely followed by bearing wear with an RPN of 224. Scientifically, this study contributes a tailored risk-priority framework that maps the ways in which environmental stressors accelerate mechanical degradation under excessive loads. Industrially and operationally, this research delivers a predictive maintenance roadmap and prioritized intervention schedule for RMU operators. Shifting the paradigm from reactive "fix-when-broken" habits to targeted maintenance prevents catastrophic motor failure, minimizes operational downtime, and eliminates costly total replacements, thereby safeguarding local food security and rural economic stability.